2014
DOI: 10.4081/pmc.2014.17
|View full text |Cite
|
Sign up to set email alerts
|

Lung abscess in a child secondary to Mycoplasma pneumoniae infection

Abstract: Lung abscess is a very rare infectious condition in children and is most commonly encountered as a complication of bacterial pneumonia. We present a case of a lung abscess in a child 6-year-old admitted with a history of right hemithorax pain lasting for 15 days and the onset of mild fever in the last two days. Etiological research showed positivity of IgM antibodies to Mycoplasma pneumoniae after seven days of admission. The child has been successfully treated with antibiotic therapy, without the use of macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In immunocompromised or aspiration patients, several Gram-negative bacteria have been identified, such as Pseudomonas aeruginosa and Klebsiella pneumoniae [ 3 ]. Nevertheless, other rare aetiologies can be encountered such as that identified by Ruffini et al, (2014) who showed that a Mycoplasma pneumoniae infection might predispose to severe infections caused by typical respiratory pathogens [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In immunocompromised or aspiration patients, several Gram-negative bacteria have been identified, such as Pseudomonas aeruginosa and Klebsiella pneumoniae [ 3 ]. Nevertheless, other rare aetiologies can be encountered such as that identified by Ruffini et al, (2014) who showed that a Mycoplasma pneumoniae infection might predispose to severe infections caused by typical respiratory pathogens [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mycoplasma infection can als cause abscess. [5] Parenteral antibiotics combined wit physiotherapy are the first line of treatment for a lun abscess. [6] Although long courses of intravenou antibiotics have been used successfully for many years, th evolution of interventional radiology has seen the use o percutaneously placed 'pigtail catheters' inserted unde ultrasound and computed tomography guidance become th mainstay of therapy where such resources are available, a it reduces the duration of injectable antibiotics.. [7] Our cas responded to medical management alone but few cases require surgical intervention.…”
Section: Introductionmentioning
confidence: 99%